Superfudge - Blume, Judy. (New York : Bantam Doubleday Dell Books for Young Readers, 1991)
Peter describes the highs and lows of life with his younger brother, Fudge.
"A Yearling book.".
Elem. School Library Collection.
Publisher's Weekly.
School Library Journal.
4.2
3-6
Keywords: Brothers -- Fiction; Family life -- Fiction; Humorous stories; Brothers -- Fiction; Family life -- Fiction; Humorous fiction